The Application of Phrase Writing Formulas to Improve Argumentative Clarity of Thai EFL Students - Zamharira, Rupa Saluja; Syahputra, Bambang Panca (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to improve the argumentative clarify of EFL student at Muslim Satun Wittaya School through the application of a systematically designed phrase writing formula. The background of this study stems from the difficulties experienced by students in writing argumentative texts due to differences in the linguistic structures of Malay, Thai, and English, which often cause language interference. The research method used was Classroom Action Research (CAR) conducted in two cycles involving 25 high school sophomore students. Data were collected through writing tests, teacher and student observation sheets, field notes, and documentation. The results show a significant improvement in students’ argumentative writing skills. The average writing score increased from 46.80 in the pre-cycle to 56.04 in Cycle I, and jumped to 85.48 in Cycle II. Teacher activity also increased from a score of 69 to 94, while student activity rose from 73.64 to 86.04. These findings prove that the phrase writing formula can function as effective scaffolding in helping students construct clearer, more coherent, and structured arguments. This study recommends the use of phrase formulas as a pedagogical strategy in argumentative writing instruction in a multilingual EFL context